INNOVATION OF TRAINING DESIGN TO INCREASE WRITING SKILL OF SCIENTIFIC ARTICLES FOR PARTICULAR FUNCTIONAL CIVIL SERVANTS THROUGH THE “REVERSE THINKING” METHOD - Endan Suwandana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aims at creating, implementing dan examining a training design innovation, whether or not it can improve the ability of the trainees. The study was carried out using descriptive-quantitative approach. This study has successfully created a training design called the Reverse Thinking (RT) method. That training design was then applied to the Article Writing Training at the Education and Training Center of the Central Statistics Bureau, attended by widyaiswara and statisticians with a total of 95 participants divided into two batches. The RT method has proven to be very effective in improving the ability of trainees to write scientific articles, both in terms of cognitive, affective, and psychomotoric (practical) aspects. Some indicators were that almost 100% of the trainees successfully submitted their papers to scientific journals on the last day of the training, evenmore 28 articles finally being published. The cognitive abilities of the participants also improved, indicated by the increase of the post-test scores. In the affective aspect, all participants have stated that their motivation in writing articles increased, as shown by the concentrated value between 7 and 10, from the 1 – 10 Likert Scale. Those results proved that the RT method could effectively improve competence of the training participants, both teoritically and practically.